Portfolio Diversification and Dynamic Interactions between Clean and Dirty Energy Assets - Belkhir, Nadia; Masmoudi, Wafa Kammoun; Loukil, Sahar; Belguith, Rihab (International Journal of Energy Economics and Policy, 2024)
Clean energy, with its focus on environmental sustainability and efficiency, has gained significance as concerns over the impact of traditional energy growth. However, there is limited evidence on the value of clean energy investments. This paper explores the role of clean energy in a balanced investment portfolio by examining two traditional energy assets (crude oil and natural gas) and two clean energy assets (SPDR S&P Kensho Clean Power ETF and iShares Global Clean Energy ETF). Using a time-varying parameter vector autoregression (TVP-VAR) model on daily data from October 2021 to January 2024, we analyze the evolving connectedness between these assets. Our results highlight dynamic interactions, with green finance indices like CNRG acting as net shock transmitters, while traditional energy indices, such as WTI and gas, primarily receive shocks. The analysis suggests that green assets, particularly ICLN, enhance portfolio stability and hedging efficiency, especially in minimum correlation and risk parity portfolios. Fossil fuels, especially gas, exhibit higher volatility, requiring careful portfolio management. Ultimately, integrating ESG criteria and adapting investment strategies to market conditions may enhance responsible investing and long-term value creation.